Qualities of Restless Legs Syndrome and Periodic Limb Movements - Bentley, Alison J (My University, 2008)
ABSTRACT The two disorders of Restless Legs Syndrome (RLS) and Periodic Limb Movements (PLM) are well recognised as fairly common neurological disorders. The presentation is of a sensory and motor component suggestive of a state of hyperexcitability of the nervous system. The underlying abnormality is believed to involve a dopamine deficiency but many of characteristics of the disorders have not been adequately described or quantified. I investigated, firstly, the possible reasons for the gender bias in the prevalence studies and found that women were more likely to have some associated conditions which may be related to RLS as well as a higher symptom load when compared to men subjects with RLS. I then looked at the problems of analysing the sensations occurring in RLS. Due to the lack of an adequate measuring tool and the possibility of a relationship between the sensations of RLS and those of pain, I used a validated descriptive pain questionnaire (the McGill pain questionnaire) to measure the sensations of RLS. Subjects with RLS were able to describe the sensations with the pain questionnaire and severity indices calculated from the McGill correlated well with measures of RLS severity but not with other intensity measures for pain. In the area of motor events I investigated the possibility of creating a classification system for the muscle activations documented as PLM. I recorded multiple muscle groups in the legs during sleep and devised a classification using sequence of activation and timing of activations from the different muscles. I also used the classification to show subtle changes in the leg activation patterns associated with change in sleep stage.
Keywords: gender differences; sleep disruption; sensory measurement; McGill pain questionnaire; motor patterns; electromyography